N-Methyl-N-nitroso-p-toluenesulfonamide - Rai, Kartik (International Union of Crystallography, 2014)
The crystal structure of the title compound, C(8)H(10)N(2)O(3)S, displays predominant C—H⋯O hydrogen-bonding and π–π stacking interactions. The hydrogen bonds are between the O atoms of the sulfonyl group and H atoms on methyl groups. The π–π stacking interactions occur between adjacent aromatic rings, with a centroid–centroid distance of 3.868 (11) Å. These interactions lead to the formation of chains parallel to (101).